Keratinocytes as sensors and central players in the immune defense against Staphylococcus aureus in the skin. Issue 3 (September 2017) - Bitschar, Katharina; Wolz, Christiane; Krismer, Bernhard; Peschel, Andreas; Schittek, Birgit
Abstract: Healthy human skin provides an effective mechanical as well as immunologic barrier against pathogenic microorganisms with keratinocytes as the main cell type in the epidermis actively participating and orchestrating the innate immune response of the skin. As constituent of the outermost layer encountering potential pathogens they have to sense signals from the environment and must be able to initiate a differential immune response to harmless commensals and harmful pathogens. Staphylococci are among the most abundant colonizers of the skin: Whereas Staphylococcus epidermidis is part of the skin microbiota and ubiquitously colonizes human skin, Staphylococcus aureus is only rarely found on healthy human skin, but frequently colonizes the skin of atopic dermatitis (AD) patients. This review highlights recent advances in understanding how keratinocytes as sessile innate immune cells orchestrate an effective defense against S. aureus in healthy skin and the mechanisms leading to an impaired keratinocyte function in AD patients.